2020
DOI: 10.1016/j.celrep.2020.107567
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Import Complex MIM Functions as Main Translocase for α-Helical Outer Membrane Proteins

Abstract: Highlights d Mitochondrial MIM complex as main translocase for a-helical outer membrane proteins d The MIM complex promotes import of signal-anchored and tail-anchored proteins d The MIM complex forms three dynamic populations d MIM and SAM complexes cooperate in the assembly of the TOM complex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 66 publications
0
64
0
1
Order By: Relevance
“…Most studies on these proteins were carried out using the ADP/ATP carrier (AAC) as a model protein. However, other proteins have been described as additional Tom70 substrates, namely the β-barrel proteins of the mitochondrial outer membrane, single- and multi-membrane-spanning (polytopic) proteins and some non-canonical carriers [ 93 , 94 , 95 , 96 , 97 , 98 ]. Hence, the substrates of Tom70 are obviously diverse, but most of these proteins contain highly hydrophobic domains and thus have the tendency to aggregate outside their target membrane.…”
Section: Functions Of Tom70 In the Biogenesis Of Mitochondrial Promentioning
confidence: 99%
“…Most studies on these proteins were carried out using the ADP/ATP carrier (AAC) as a model protein. However, other proteins have been described as additional Tom70 substrates, namely the β-barrel proteins of the mitochondrial outer membrane, single- and multi-membrane-spanning (polytopic) proteins and some non-canonical carriers [ 93 , 94 , 95 , 96 , 97 , 98 ]. Hence, the substrates of Tom70 are obviously diverse, but most of these proteins contain highly hydrophobic domains and thus have the tendency to aggregate outside their target membrane.…”
Section: Functions Of Tom70 In the Biogenesis Of Mitochondrial Promentioning
confidence: 99%
“…Therefore, in yeast cells, the targeting information of TA7 could be ambiguous and be recognized both as a mitochondrial and a peroxisomal signal. Similarly to Gem1 [15,17], TA7 is the only T. vaginalis protein requiring the MIM complex for its insertion. Since an orthologue of such a complex has not been identified yet in hydrogenosomes, most probably a complex without sequence similarity to the Mim proteins mediates the integration of TA7 to the hydrogenosomes membrane.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that in yeast cells, HA-TA4 assumes in both ER and mitochondria a topology with the N-terminal soluble domain facing the lumen or the IMS, respectively. Recently, it has been observed that the MIM complex is required for the insertion of singlespan proteins, including the TA protein Gem1, into the MOM [15,17]. Therefore, we tested whether the deletion of Mim1, the central component of the MIM complex, affects the mitochondrial levels of HA-TA4.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Many mitochondrial proteins, however, lack presequences and embark on other import routes into mitochondria. This is the case for all proteins of the outer membrane and most components of the intermembrane space (IMS) which employ several distinct pathways (Doan et al, 2020;Drwesh and Rapaport, 2020;Edwards et al, 2020;Finger and Riemer, 2020;Wiedemann and Pfanner, 2017). In addition, many mitochondrial inner membrane proteins, in particular the members of the metabolite carrier family (carriers for short) lack presequences and are imported via a distinct 'carrier pathway' (Horten et al, 2020;Rehling et al, 2004).…”
Section: Introductionmentioning
confidence: 99%